Cyclic RGD peptidomimetics containing 4- and 5-amino-cyclopropane pipecolic acid (CPA) templates as dual αVβ3 and α5β1 integrin ligands. Issue 4 (15th February 2016) - Sernissi, Lorenzo; Trabocchi, Andrea; Scarpi, Dina; Bianchini, Francesca; Occhiato, Ernesto G.
Graphical abstract: Abstract: 4-Amino- and 5-amino-cyclopropane pipecolic acids (CPAs) with cis relative stereochemistry between the carboxylic and amino groups were used as templates to prepare cyclic peptidomimetics containing the RGD sequence as possible integrin binders. The peptidomimeticc(RGD8) built on the 5-amino-CPA displayed an inhibition activity (IC50  = 2.4 nM) toward the αv β3 integrin receptor (expressed in M21 human melanoma cell line) comparable to that of the most potent antagonists reported so far and it was ten times more active than the corresponding antagonistc(RGD7) derived from the isomeric 4-amino-CPA. Both compounds were also nanomolar ligands of the α5 β1 integrin (expressed in human erythroleukemia cell line K562). These results suggest that the CPA-derived templates are suitable for the preparation of dual αv β3 and α5 β1 ligands to suppress integrin-mediated events as well as for targeted drug delivery in cancer therapy.